Party cohesion in the Icelandic Althingi - Kristinsson, Gunnar Helgi (Stjórnsýslustofnun, 2011)
Institutional theories of party cohesion may be divided into "nomination theories" and "structure of the executive theories". The former seek explanations of cohesion in the way nominations are conducted, predicting that de-centralized and inclusive nominations will reduce party cohesion. The latter attempt to explain cohesion by reference to the structure of the executive, and predict that parliamentary government will increase cohesion. Party cohesion in the Icelandic Althingi has, hitherto, not been extensively studied. In this article, large amounts of data are explored to test hypotheses derived from the two theoretical approaches. The analysis is based on roll-call data dating back to 1961 and electronic voting records from 1991 onwards. The main conclusion is that party cohesion is at a high level in Iceland, despite decentralized and inclusive nominations, and hypotheses derived from nomination theories therefore find no support in our data. Hypotheses derived from "structure of the executive theories" fare much better and the main reason for high party cohesion in Iceland seems to be parliamentary government. Various features of our data, however, encourage us not to ignore other contextual features affecting party cohesion, which neither of the two institutional theories can account for satisfactorily.